Enhancing water distribution system security through water quality mobile sensor operation - Perelman, Lina; Wan Salim, Wan Wardatul Amani; Wu, Rouxi; Park, Joonhyeong; Ostfeld, Avi; Banks, M. Katherine; Porterfield, D.M (American Society of Civil Engineers ( ASCE ), 2013)
Recent developments in wireless/wired sensor networks allowed the application of stationary sensors capable of continuously collecting and transmitting hydraulic and water quality measurements at fine temporal resolution. The constantly updating data allows achieving an improved representation of the system state, modeling, and control. The deployment of fixed water quality sensors in water distribution systems has been recognized to be the key component of contamination warning systems for securing public health. This study proposes to explore how the inclusion of mobile sensors monitoring for various water quality parameters (i.e., pH, water hardness, and disinfectant) can enhance water distribution systems security. Mobile sensors equipped with sampling, sensing, data acquisition, wireless transmission, and power generation systems are being designed, fabricated, and tested with prototypes expected to be released in the very near future. Ideally, these mobile sensors will act as mobile agents capable of continuously conducting multivariate measurements and reporting them as they are distributed with water pipe flow. This work initiates the development of a theoretical mathematical framework for modeling mobile sensor movement in the water distribution system, processing and integrating the sensory data collected from stationary and nonstationary sensor nodes to increase system reliability and security through increasing coverage and reducing fault detection time.